DO CLASSROOM EXPERIMENTS INCREASE STUDENT MOTIVATION? A PILOT STUDY - Hans Gremmen; Gijs van den Brekel (European Scientific Journal, ESJ, 2013)
More and more teachers of economics use classroom experiments as one of their didactic tools. Classroom experiments are short exercises in which students interact in a game-like setting that was designed to facilitate their understanding of key economic ideas. Can classroom experiments be used to boost student interest in economics, promote greater university enrollment and lower dropout rates? This paper presents a design encompassing five measures for motivation based on student behavior, to explore whether the use of classroom experiments in economics courses stimulates students to study economics. It then describes a pilot study devised to apply this design to a sample of Dutch preuniversity students. Analysis of the results reveals a positive and significant treatment effect for four of the five measures. Further research applying the design more extensively should reveal whether our findings have general validity.